Ethiopia Economic Update 7 : Special Topic - Poverty and Household Welfare in Ethiopia, 2011-16 - World Bank (World Bank, Washington, DC, 2019)
Ethiopia’s real gross domestic product (GDP) growth, while still strong, decelerated to 7.7 percent in FY2018. A slowdown in industrial growth, mainly driven by lower growth in construction due to foreign exchange shortages and higher prices of imported construction materials, coupled with weaker performance of the manufacturing and the agriculture sectors, explains to a large extent the growth deceleration. Services sector exhibited strong growth in FY2018 while manufacturing underperformed. Poverty in Ethiopia deceased substantially over the past decade, although by less than what would have been expected based the country’s on strong economic growth. This special topic complements the government’s interim report on 2015-2016 poverty analysis study, by taking a closer look at some of the household-level welfare trends between 2011 and 2016.